The Origin of Fluorescence from Graphene Oxide - Shang, Jingzhi; Ma, Lin; Li, Jiewei; Ai, Wei; Yu, Ting; Gurzadyan, Gagik G. (Scientific reports, 2012)
Time-resolved fluorescence measurements of graphene oxide in water show multiexponential decay kinetics ranging from 1 ps to 2 ns. Electron-hole recombination from the bottom of the conduction band and nearby localized states to wide-range valance band is suggested as origin of the fluorescence. Excitation wavelength dependence of the fluorescence was caused by relative intensity changes of few emission species. By introducing the molecular orbital concept, the dominant fluorescence was found to originate from the electronic transitions among/between the non-oxidized carbon regions and the boundary of oxidized carbon atom regions, where all three kinds of functionalized groups C-O, C = O and O = C-OH were participating. In the visible spectral range, the ultrafast fluorescence of graphene oxide was observed for the first time.